Serum aminotransferase activity in patients of epilepsy and mania taking sodium valproate. - Khubchandani, Asha; Parmar, Vijay R; Jadav, Janki; Sidhu, Gagandeep; Solanki, Viral; Gangwani, Sagar; Solanki, Meghna (Annals of Pathology and Laboratory Medicine, 2014)
Background: Our aim is to study the serum aminotransferase activity in patients of epilepsy and mania taking sodium valproate.Â Sodium valproate is a common drug to be prescribed to the patients of epilepsy and mania. Aminotransferase, both AST (Aspartate amino transferase) and ALT (Alanine amino transferase) is an accepted marker for any liver injury. Methods:Â Serum sample of fifty patients of known cases of epilepsy and mania, who were on sodium valproate since at least 3 month and fifty normal subjects were taken. Serum aminotransferase level (both AST & ALT) were estimated by colorimetric method in fully automated Erba XL-640 Analyser. Results: The level of aminotransferase enzymes wereÂ increased in patients of epilepsy and mania after administration of sodium valproate and elevation was highly significantÂ as compared to the normal subjects (p value <0.05). Conclusion: From our study it is concluded that there is a need for monitoring serum aminotransferase level in patients receiving sodium valproate.